Cryptococcus: isolamento ambiental e caracterização bioquímica - Araújo Júnior, Erivelto Correa da [UNESP]; Táparo, Cilene Vidovix [UNESP]; Uchida, Cyndi Yuri [UNESP]; Marinho, Márcia [UNESP] (FapUNIFESP (SciELO), 2015)
Cryptococcosis is an opportunistic fungal infection caused by Cryptococcus yeasts, especially C. neoformans and Cryptococcus gattii. The fungus is found in substrates of animal and vegetable origin, and infection occurs through inhalation and seedlings present in the environment. The present study aimed to investigate the existence of microfocus Cryptococcus sp. from the environmental samples of Araçatuba city, São Paulo, featuring new niches, by decoupling the direct relationship between fungus and host in order to minimize the risk of contamination of man and animals, understanding the ecoepidemiology of Cryptococcus. Fifty samples from hollows and tree trunks were harvested (Cassia sp., Ficus sp., Caesalpinea peltophorides) from ten representatives in the urban perimeter. The samples were immediately sent to the Laboratory of Bacteriology and Mycology, Faculty of Veterinary Medicine Araçatuba - Unesp where they were processed and plated on Petri dishes containing agar seed Niger and Sabouraud dextrose agar with chloramphenicol, incubated at 30ºC for a period of no less than 5 days. Afterwards they were subimitted to biochemical tests: urease production, thermotolerance at 37°C and quimiotipagem in CGB agar (L- Canavanine-Glycine-Bromothymol blue). The results showed that 17 (34%) cultures were positive for Cryptococcus, 9 (18%) for Cryptococcus gattii and 8 (16%) for Cryptococcus neoformans. Other yeast correlated as Rhodotorula sp. and Candida sp. were isolated. We conclude that the infectious propagules of Cryptococcus are dispersed in nature and constitute an environmental microfocus, not necessarily being bound to a single host.

O gênero Cryptococcus caracteriza-se por ser uma levedura responsável por infecção sistêmica, causada pelas espécies Cryptococcus neoformans e Cryptococcus gattii. O fungo é encontrado em substratos de origem animal e vegetal, e a infecção ocorre com a inalação de basidiósporos ou leveduras desidratadas infectantes presentes no ambiente. O presente trabalho teve por objetivo pesquisar a existência de microfocos de Cryptococcus sp.em amostras ambientais da cidade de Araçatuba, São Paulo, com a finalidade de minimizar os riscos de contaminação do homem e dos animais, buscando o conhecimento da ecoepidemiologia do Cryptococcus. Foram colhidas 50 amostras oriundas de ocos e troncos de árvores (Cassia sp., Ficus sp., Caesalpinea peltophorides) de 10 locais representativos do perímetro urbano, as quais foram encaminhadas ao Laboratório de Bacteriologia e Micologia da Faculdade de Medicina Veterinária de Araçatuba-Unesp, onde foram processadas e semeadas em placas de Petri contendo ágar semente de Níger e Sabouraud dextrose com clorafenicol e incubadas à temperatura de 30ºC, por um período não inferior a cinco dias. Posteriormente, foram submetidas às provas bioquímicas: produção de urease, termotolerância a 37ºC e quimiotipagem em ágar CGB (L-canavanina-glicina-azul de bromotimol). A análise dos resultados revelaram que 17 (34%) dos cultivos foram positivos para o gênero Cryptococcus, sendo nove (18%) para Cryptococcus gattii e oito (16%) para Cryptococcus neoformans. Outras leveduras correlacionadas, como Rhodotorula sp. e Candida sp., também foram isoladas. Conclui-se que os basidiósporos de Cryptococcusencontram-se dispersos na natureza, constituindo microfocos ambientais, não vinculados necessariamente a um único hospedeiro.
Cryptococcus: environmental isolation and biochemical characterization
Keywords: Tree; Cryptococcosis; Environmental microbiology; Microfocus; Árvore; Criptococose; Microbiologia ambiental; Microfocos